Calcium fluoride based multifunctional nanoparticles for multimodal imaging - Straßer, Marion; Schrauth, Joachim H. X.; Dembski, Sofia; Haddad, Daniel; Ahrens, Bernd; Schweizer, Stefan; Christ, Bastian; Cubukova, Alevtina; Metzger, Marco; Walles, Heike; Jakob, Peter M.; Sextl, Gerhard (Beilstein Journal of Nanotechnology, 2017)
New multifunctional nanoparticles (NPs) that can be used as contrast agents (CA) in different imaging techniques, such as photoluminescence (PL) microscopy and magnetic resonance imaging (MRI), open new possibilities for medical imaging, e.g., in the fields of diagnostics or tissue characterization in regenerative medicine. The focus of this study is on the synthesis and characterization of CaF2:(Tb3+,Gd3+) NPs. Fabricated in a wet-chemical procedure, the spherical NPs with a diameter of 5–10 nm show a crystalline structure. Simultaneous doping of the NPs with different lanthanide ions, leading to paramagnetism and fluorescence, makes them suitable for MR and PL imaging. Owing to the Gd3+ ions on the surface, the NPs reduce the MR T1 relaxation time constant as a function of their concentration. Thus, the NPs can be used as a MRI CA with a mean relaxivity of about r = 0.471 mL·mg−1·s−1. Repeated MRI examinations of four different batches prove the reproducibility of the NP synthesis and determine the long-term stability of the CAs. No cytotoxicity of NP concentrations between 0.5 and 1 mg·mL−1 was observed after exposure to human dermal fibroblasts over 24 h. Overall this study shows, that the CaF2:(Tb3+,Gd3+) NPs are suitable for medical imaging.
Keywords: calcium fluoride nanoparticles; magnetic resonance imaging (MRI); multifunctional nanoparticles; multimodal imaging; photoluminescence